O Sistema Interamericano de Proteção aos Direitos Humanos e a reforma psiquiátrica brasileira: reflexões acerca do impacto causado pelo caso Damião Ximenes Lopes - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The present thesis is proposed to verify the existence of an influence relation between the case of Ximenes-Lopes v. Brazil filled before the Inter-American System for the protection of Human Rights by violation of the human rights embodied in the American Convention on Human Rights, and the pending legislative process of the law project of the Psychiatric Reform, in the two houses of the National Congress. The research has qualitative, descriptive and exploratory nature, having as its methodological procedures the bibliographic and documentary research. In the first chapter is approached the fact object that is the discussion generator in this thesis: the death of Damião Ximenes Lopes, who had psychiatric disturbs developed by abusive treatment, and; the private institution, acting in a State capacity, to give medical assistance of this nature. In the second chapter, as it demands, the internationalization of Human Rights post the Second World War is described, verifying the tendency of creating documents and international organs related to the thematic, as well, the inspection and sanctioning of the States that would violate those prerogatives, as the Inter-American System of the Human Rights. In the third chapter, the case Ximenes-Lopes is analyzed towards the Inter-American System, prevailing the arguments brought by the Brazilian State to justify the facts and actions due to the events. The forth chapter report the national conjuncture in reference of the support given by the social security politics since the beginning of the Military Regime (1964) until the government measures to implant a Sanitary Reform, in the transition process, consubstantiate in the establishment of the Uniform Health System from the Constitution in 1988, to the beginning of the practice government measures, in favor of its effectiveness in 1993. The fifth chapter approaches the Psychiatric Reform itself, since the imperial conjuncture of the effective treatment up to the moment of the proposition of the Law Project auspicious in the necessary changes. In this chapter to discourse about the legislative process the influence relation of the Ximenes-Lopes case is approached in its acceleration and approval. In the final considerations, from the inferences built during the methodological course, the results of the study lead to point that there was influence in the case Ximenes-Lopes v. Brazil filled before the Inter-American Human Rights System due to the pending legislative process and the approval of the Federal Law No. 10.216 in April 6th, 2001, known as the Psychiatric Reform Law.
Keywords: Direitos Humanos; Sistema Interamericano de Proteção aos Direitos Humanos; Damião Ximenes Lopes; Reforma Psiquiátrica; Human Rights; Inter-American System for the protection of human rights; Ximenes-Lopes; Psychiatric Reform; CNPQ::CIENCIAS SOCIAIS APLICADAS